The theory of general static equilibrium - Fossati, Eraldo; Shackle, G.L.S. (Oxford : B. Blackwell, 1957)
The book aims to present a picture of Pareto's theory of general equilibrium interpreted as the limit case of dynamics. This view is the natural consequence of the position the author took up more than twenty years ago, that it is not possible to break the logical unity of economic analysis, and to treat dynamics, as was usual in those days, as merely the theory of business cycles. When the two kinds of theory are thus separated, the theory of general equilibrium is called upon to explain only the determination of the quantities and prices at one instant of time in a system of general mutual dependence of variables, while the theory of business cycles tells us only about the cumulative process of development of these quantities and price through time, without explaining how they are determined.
"Prepared from the fourth Italian enlarged edition of Professor Fossati's Elementi di economia razionale."--Dust jacket.
Includes bibliographical references and index.
rpm 07/11/2017
Loans
Keywords: Economics